Linguostylistic Analysis of Conceptual Structure in Literary Works - Rahmatova Sitora Samadovna; Arustamyan Yana Yurievna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
Abstract: Linguostylistics, as a bridge between linguistics and literary criticism, offers a systematic framework for examining how language constructs and reveals conceptual structures in literary texts. This paper integrates traditional linguostylistic methods with cognitive approaches, particularly Conceptual Metaphor Theory and Conceptual Blending Theory, to analyze how abstract concepts such as love, identity, time, freedom, and the self are linguistically realized and stylistically foregrounded in literary works. Drawing on the principles of cognitive stylistics, the study demonstrates that conceptual structures are not merely ornamental but form the cognitive backbone of literary meaning-making, influencing reader interpretation through metaphorical mappings, lexical choices, syntactic patterns, and stylistic devices.